Forest and Landscape Restoration: A Review Emphasizing Principles, Concepts, and Practices - César, Ricardo Gomes; Belei, Loren; Badari, Carolina Giudice; Viani, Ricardo A. G.; Gutierrez, Victoria; Chazdon, Robin L.; Brancalion, Pedro H. S.; Morsello, Carla (Land (Basel), 2021)
Forest and Landscape Restoration (FLR) is considered worldwide as a powerful approach to recover ecological functionality and to improve human well-being in degraded and deforested landscapes. The literature produced by FLR programs could be a valuable tool to understand how they align with the existing principles of FLR. We conducted a systematic qualitative review to identify the main FLR concepts and definitions adopted in the literature from 1980 to 2017 and the underlying actions commonly suggested to enable FLR implementation. We identified three domains and 12 main associated principles—(i) Project management and governance domain contains five principles: (a) Landscape scale, (b) Prioritization, (c) Legal and normative compliance, (d) Participation, (e) Adaptive management; (ii) Human aspect domain with four principles: (a) Enhance livelihoods, (b) Inclusiveness and equity, (c) Economic diversification, (d) Capacity building; (iii) Ecological Aspects domain with three principles: (a) Biodiversity conservation, (b) Landscape heterogeneity and connectivity, (c) Provision of ecosystem goods and services. Our results showcase variations in FLR principles and how they are linked with practice, especially regarding the lack of social aspects in FLR projects. Finally, we provide a starting point for future tools aiming to improve guidance frameworks for FLR.